2017
DOI: 10.1155/2017/7038789
|View full text |Cite
|
Sign up to set email alerts
|

Actinidia chinensis Planch. Improves the Indices of Antioxidant and Anti‐Inflammation Status of Type 2 Diabetes Mellitus by Activating Keap1 and Nrf2 via the Upregulation of MicroRNA‐424

Abstract: The fruit juice of Actinidia chinensis Planch. has antioxidant and anti-inflammation properties on patients with type 2 diabetes mellitus (T2DM), but the molecular mechanism was unclear. The patients took the juice and the serum level of antioxidant miR-424, Kelch-like ECH-associated protein 1 (Keap1), erythroid-derived 2-like 2 (Nrf2), and biochemical indices were measured. The juice increased the levels of serum microRNA-424, Keap1, and Nrf2 and reduced the levels of interleukin-1 (IL-1) beta and IL-6 in T2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…One study enrolled hypercholesterolemic subjects 20. Two trials were conducted in hypertensive patients,26,29 one each in T2DM28 and male smokers 27. Study period ranged from 4 weeks to 9 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study enrolled hypercholesterolemic subjects 20. Two trials were conducted in hypertensive patients,26,29 one each in T2DM28 and male smokers 27. Study period ranged from 4 weeks to 9 months.…”
Section: Resultsmentioning
confidence: 99%
“…Three trials used kiwifruit of A. deliciosa ,20,27,29 and one study each used kiwifruit juice of A. chinensis 28 and kiwifruit capsules 26. Four studies practically evaluated kiwifruit vs placebo,20,26–28 although in two studies healthy or habitual diet was followed in both the treatment and the control groups 20,27. One study assessed kiwifruit against apple 29.…”
Section: Resultsmentioning
confidence: 99%
“…Next interesting dietary intervention revealed that the fruit juice of Actinidia chinensis planch (kiwi fruit) has antioxidant and anti-inflammatory properties in patients with T2DM. After 9 months of intervention, increased expression of miR-424, Keap1, and Nrf2 along with reduced levels of IL-1 β and IL-6 were reported in T2DM patients [294]. Likewise, there is an evidence that high consumption of dietary fructose is a major contributor to MetS.…”
Section: Microrna In Mets-a Link With Chronic Inflammation Related Tomentioning
confidence: 99%
“…Results showed that the levels of Rictor and p-Akt in high-glucose Previous reports showed that miR-424 was downregulated in patients with Type 1 diabetes (Cao et al, 2018), demonstrating that miR-424 may function as a potential biomarker with applications in the clinical setting. The upregulation of miR-424 could improve the antioxidant and anti-inflammation status in patients with diabetes (Sun, Li, Li, Dai, & Tan, 2017) for therapeutic application. On the basis of these studies, we found miR-424 upregulation had a beneficial role to recover the renal lesion in Type I diabetes models.…”
Section: Upregulation Of Mir-424 Inhibited Mtorc2/akt Signaling In mentioning
confidence: 99%